Vocational rehabilitation assistive technology, access, supported employment, and employment outcomes for transition-aged young adults with cognitive disabilities - Alshamrani, Khalid, author; Graham, James, advisor; Roll, Marla, advisor; Jennings, Louise, committee member; Sharp, Julia, committee member (Colorado State University. Libraries, 2024)
Objective: The purpose of this dissertation was to conduct three research studies aimed at understanding the barriers and facilitators to equitable access to vocational rehabilitation (VR) assistive technology (AT), its utilization in supported employment (SE), and the resulting competitive integrated employment (CIE) outcomes of transition-aged young adults (TAYA) with cognitive disabilities. Introduction: TAYA with disabilities face significantly higher rates of unemployment and underemployment than their peers without disabilities. For TAYA with cognitive disabilities, these disparities are even more pronounced, making them one of the most excluded groups from the labor force. Despite cognitive disabilities being the largest disability group served by state VR programs, this population continues to face poor employment outcomes upon exiting these programs. Although there is growing evidence of AT's potential to improve employment outcomes, AT support remains underutilized for TAYA with cognitive disabilities, with notable disparities in its utilization. Methods: Study One employed a retrospective cross-sectional study using Rehabilitation Services Administration Case Service Report (RSA-911) data from 2017 to 2019, a period before the COVID-19 pandemic impacted state VR service operations. Multivariable logistic regression analysis was conducted to examine the main and interaction effects of various sociodemographic variables commonly considered in disparities research on the likelihood of receiving AT services among TAYA with disabilities participating in state VR programs. This study provides a baseline understanding of disparities and access to AT services among TAYA with disabilities served by state VR programs in a pre-pandemic context. Study Two was a qualitative study. We conducted focus groups to gather insights from four key stakeholder groups—VR policymakers and funders, VR service providers, employers, and TAYA with cognitive disabilities and their families. The focus was on exploring their perspectives and experiences related to the transition to virtual support and how TAYA with cognitive disabilities accessed and utilized AT devices and services for facilitating their CIE during and following the COVID-19 pandemic. All focus group sessions were held virtually and video recorded and analyzed using thematic analysis. Study Three was another retrospective cross-sectional study using RSA-911 data from July 2017 to June 2022. We investigated how the receipt of AT and/or SE services was independently associated with obtaining CIE at program exit, and how the probabilities of achieving CIE varied across the pre-COVID, during COVID, and post-COVID periods among TAYA with cognitive disabilities served by state VR programs. Multivariable logistic regression analysis was used to calculate odds ratios for the likelihood of obtaining CIE at program exit among TAYA with cognitive disabilities who received the two VR services (AT, SE). To assess whether the relationships between these two VR services and CIE outcomes varied over time, interaction terms between the COVID-19 pandemic periods variable (pre-, during, and post-pandemic) and the two VR services of interest were included in the model. Results: Study One revealed that less than 3% of TAYA with disabilities received AT services. The following client characteristics were associated with a lower likelihood of receiving AT services for TAYA with disabilities: unemployed, minority, significant disability, older in age, TAYA with mental and cognitive disabilities, and not enrolled in PSE. Study Two identified key findings from focus group sessions, highlighting positive overall experiences with using mainstream mobile devices and applications. Areas for improvement beyond the pandemic include enhancing AT access through state Medicaid waivers, providing VR providers with training opportunities to deliver effective AT support to TAYA with cognitive disabilities seeking CIE who need and could benefit from such support, and ensuring the technology employed and used is accessible and usable by this population. In Study Three, more than half (55.9%) of TAYA with cognitive disabilities in the study sample did not achieve CIE at program exit. Only 1.4% received AT services and 10.7% received SE services. Overall, the receipt of AT and SE showed positive and significant associations with achieving CIE at program exit compared to those who did not receive these services. In addition, there were higher probabilities of achieving CIE outcomes during and post-COVID compared to the pre-COVID period. Conclusion: The findings from this dissertation highlight the underutilization of AT support among TAYA with disabilities served by state VR programs, particularly in addressing their job-seeking needs and transitions from education to CIE. The shift to virtual support, accelerated by the COVID-19 pandemic, increased access to mainstream mobile devices and applications for TAYA job seekers with cognitive disabilities. Before the COVID-19 pandemic, AT support access was primarily focused on supporting TAYA with cognitive disabilities who were participating in academic programs or being employed for job retention, with limited AT support for job seekers. During the pandemic, however, TAYA job seekers with cognitive disabilities had access to mainstream mobile devices and applications within the VR system. Such access allowed this population to acquire skills in using mobile devices and applications for pursuing their CIE opportunities, access job training resources, continue receiving virtual supports, and engage in virtual job interviews with potential employers. The intersection of AT and SE offers an opportunity to enhance CIE outcomes for TAYA with cognitive disabilities. The probability of achieving CIE was higher among this population receiving SE and AT support during and post-COVID than pre-COVID. This underscores the need for continued efforts to improve targeted transition policies and practices, enhance the services and supports for TAYA with cognitive disabilities, and provide AT training opportunities to VR personnel who serve this population. Increasing AT training in rehabilitation educational programs and in-service training could enhance VR AT service utilization. Further research is needed to generate evidence supporting AT use in vocational settings and to develop guidelines for its incorporation into employment transition processes. Such efforts are essential to ensuring that TAYA with cognitive disabilities have equitable opportunities and the support they need for employment success.
Keywords: competitive integrated employment; supported employment; vocational rehabilitation; disabilities; assistive technology; transition-aged young adults